CONSUMER RELATED THEORIES AND THE RIGHT TO INFORMED CHOICE FOR CONSUMER IN NANO FOOD CONSUMPTION (UUM Journal of Legal Studies, 2022)
The use of nanomaterials in food-by-food producers has increased in today’s modern society. Food that contains nanomaterials is known as nano food, which is associated with both benefits and risks. Due to the uncertainty of its risks, it is important to accord consumers with the right to informed choice in the context of nano food consumption. In the absence of this right in the existing food legislation in Malaysia, this paper aims to examine the underlying principles from the perspective of consumer-related theories to provide theoretical justification in reforming the present food legislation. This paper presents how the identified consume-related theories can be applied to explain the need for such rights in Malaysian legislation. Three consumer-relatedtheories, which are the Theory of Planned Behaviour, Consumerism heory, and Postmodernism Theory, are analysed through a doctrinal approach and via theory analysis. Deductive inferences were made to establish the rationale for the need to have the right of informed choice available to consumers in the context of nano food consumption. The examination of the theories evidently shows that the right to informed choice can be exercised through labelling requirements for nano food. This paper contributes significantly to the existing body of knowledge as it highlights the need for the right to informed choice for consumers in nano food consumption, and emphasises the identification of consumer-related theories to support legislative reform so as to include the right. This paper suggests the use of labelling as a way of according the right to informed choice to consumers in nano food consumption.